Significance of perforating vessels in vertebrobasilar territory acute ischemic stroke treated with mechanical thrombectomy: a review of cone-beam computed tomography findings and the literature - Md Noh, Mohamad Syafeeq Faeez; Shamsuddin Perisamy, Rajeev; Tharek, Anas; Noralam, Noor Hayatul Al Akmal; Yahya, Muhammad Zakwan; Amran, Mohd Hanif; Mah, Sin Yeat; Mohamad, Siti Azleen; Abdul Rashid, Anna Misyail; Ibrahim, Azliza; Abdul Rahim, Ezamin; Muda, Ahmad Sobri (Korean Stroke Society, 2026)
Posterior circulation ischemic stroke generally has a poor prognosis. Compared with ischemic stroke affecting the anterior circulation, few studies have discussed its management. However, the role of the perforating vessels in the vertebrobasilar territory is not well understood. In this letter, we discuss the potential significance of perforating vessels in this cerebrovascular territory in patients with acute ischemic stroke (AIS) who were treated successfully with mechanical thrombectomy (MT), with a particular focus on high-resolution cone-beam computed tomography (CT) (CBCT) imaging findings, brief aspects of clinical management, and eventual outcomes. Relevant literature was also reviewed. As an illustration, we reviewed two patients who presented to our center within 24 hours of symptom onset. Both patients were noted to have basilar artery occlusion (BAO) on pretreatment imaging and underwent MT. Despite successful revascularization in both cases, different clinical outcomes were observed, which we postulate may relate to the pre- and postMT findings within the brainstem on high-resolution intra-arterial CBCT.